TINGKAT KETERAMPILAN TEKNIK DASAR BOLA VOLI PADA USIA 13-15 TAHUN PUTRA PADA KLUB BOLA VOLI TARUNA MERAH PUTIH KOTA SEMARANG TAHUN 2021 - Kristian Pradana; Catur Wahyu Priyanto; Liska Sukiyandari (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2022)
The purpose of this study was to determine the skill level of passing down, passing over, serving and smashing male athletes aged 13-15 years at the Taruna Merah Putih club, Semarang City. This study uses a quantitative descriptive approach. Sampling used purposive sampling technique, namely male athletes aged 13-15 years, totaling 20 people. The results of this study are the bottom passing that got a value of 5 there were 11 athletes (55%), who got a value of 4 there were 3 athletes (15%), who got a value of 3 there were 6 athletes (30%), who got a value of 2 and 1 were 0 athlete (0%). There were 9 athletes (45%), who got a score of 4, 5 athletes (25%), who got a score of 3, there were 3 athletes (15%), those who got a score of 2 were 3 athletes (15%) and 1 there are 0 athletes (0%). The top service that got a score of 5 was 1 athlete (5%), those who got a value of 4 were 8 athletes (40%), those who got a score of 3 were 10 athletes (50%), those who got a score of 2 were 1 athlete (5%), who get a value of 1 there are 0 athletes (0%). Smash that got a score of 5 there were 4 athletes (20%), those who got a value of 4 were 10 athletes (50%), those who got a score of 3 were 6 athletes (30%), those who got a value of 2 and 1 were 0 athletes (0%)